A PROSPECTIVE AUDIT OF PRESCRIBING IN PARKINSON'S DISEASE. Issue 10 (9th September 2014) - Ejaz, Ayesha; Toescu, Sebastian; Nageshwaran, Sathiji; Proukakis, Christos
Abstract : Background: Patients with Parkinson's disease (PD) are at risk of complications related to incorrect prescribing when admitted to hospital. The 'Get It On Time' campaign by Parkinson's UK aims to raise awareness of inpatient prescribing issues. This prospective audit was undertaken to establish current practice in dopaminergic medication prescribing in a district general hospital (DGH). Methods: All patients with a Parkinsonian syndrome admitted over two months were included. Case notes and drug charts were reviewed at admission and while an inpatient. Correct medication regimes were identified from clinic letters and faxed primary care documents. Results: 34 patients were identified (mean age 79y). 25 patients had idiopathic PD. The majority (28 patients) were taking co-careldopa or co-beneldopa. 56% of patients had medications incorrectly prescribed at admission; 26% received doses at incorrect times. 26% of patients self-administered their medication. Although 17 patients were nil per oram, only 2 patients received medications by alternative routes. 4 patients received anti-dopaminergic medication. Conclusions: Our study highlights that greater accuracy is required in inpatient prescribing for PD. These findings are comparable to other studies. Following this audit, a talk was delivered to incoming junior doctors at the DGH regarding Parkinson's medication prescribing. We are currently re-auditing.